THE POTENCY OF MEALWORM LARVAE (Tenebrio molitor) AS BROILER FEED BASED ON PERFORMANCE, LIPID AND BLOOD CHARACTERISTICS MEASUREMENTS: A META-ANALYSIS - Harningsih, Intan Sri; Jayanegara, Anuraga; samadi, samadi (Jurnal Kedokteran Hewan, 2025)
This study was proposed to provide general conclusions regarding the potential of feeding the meal worm (Tenebrio molitor) to broiler productivity and healthy using the meta-analysis method. The research was initiated with a search for articles through the Google Scholar and Scopus databases and 1923 articles were obtained using the keywords Tenebrio molitor, mealworm, broiler chicken, performance, feed conversion ratio, broilers, caterpillars, carcasses, body weight, feed, Hongkong caterpillars connected with Boolean operators AND and OR. Furthermore, article selection was carried out based on the PRISMA flow chart using Microsoft Excel and Mendeley. The results of data extraction from 25 articles included in the meta-analysis were then processed in the form of a database in Microsoft Excel, converted to the same unit and then analyzed with mixed model procedures using Statistical Analysis System (SAS) software. The parameters measured were body weight (BW), body weight gain (BWG), average daily growth (ADG), feed consumption (FI), average daily feed intake (ADFI), feed conversion ratio (FCR), carcass weight (CW), carcass yield (CY), abdominal fat, total protein, cholesterol, glucose, uric acid, hemoglobin, erythrocytes, leukocytes, albumin, and globulin. Data from each article were tabulated in Microsoft Excel software. The results showed that the use of Tenebrio molitor as animal feed showed a quadratically significant effect in reducing BWG (62,13 g), FI (112,42 g), CY (70,47%), albumin (20,71), and UA (5,44) (P0,05). However, there was no significant effect (P0,05) on BW, ADG, ADFI, FCR, CW, abdominal fat, total protein, cholesterol, glucose, hemoglobin, erythrocytes, leukocytes, and globulin by utilizing Tenebrio molitor as broiler feed. It can be concluded that the provision of Tenebrio molitor has the potential as broiler feed. The optimal use of Tenebrio molitor in broiler chickens is 17,04%. The feeding dose must be considered because Tenebrio molitor contains antinutrients in the form of chitin and tannin to avoid negative effect on the performance and health of broiler chickens.